1997
DOI: 10.1097/00001648-199709000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Maternal Alcohol Consumption and Risk of Spontaneous Abortion

Abstract: Maternal alcoholism is known to have adverse effects on reproduction and fetal development, but the effects of moderate consumption remain controversial. In a previous case-control study, we found a doubled risk of spontaneous abortion with an average consumption of seven or more drinks per week during the first trimester. To confirm this finding while avoiding potential biases from the case-control design, we examined moderate alcohol consumption in a prospective cohort study of over 5,000 pregnant women. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 22 publications
4
72
1
1
Order By: Relevance
“…The frequency of fetal alcohol syndrome in the United States is 0.5 to 3 per 1000 births per year [144], and maternal alcohol consumption is the most commonly identified nongenetic cause of mental retardation [145]. As well as characteristic facial features and cranio-facial dysmorphology, children with fetal alcohol syndrome have microcephaly, growth restriction and central nervous system damage.…”
Section: Vip In Fetal Alcohol Syndromementioning
confidence: 99%
“…The frequency of fetal alcohol syndrome in the United States is 0.5 to 3 per 1000 births per year [144], and maternal alcohol consumption is the most commonly identified nongenetic cause of mental retardation [145]. As well as characteristic facial features and cranio-facial dysmorphology, children with fetal alcohol syndrome have microcephaly, growth restriction and central nervous system damage.…”
Section: Vip In Fetal Alcohol Syndromementioning
confidence: 99%
“…High levels of alcohol consumption in early pregnancy have been associated with increased risk of spontaneous abortion (Bailey & Sokol, 2011). The evidence for smaller amounts is uncertain (Henderson et al, 2007), but a few studies have found that the risk of spontaneous abortions increases gradually with dose of alcohol exposure in early human pregnancy (Nybo-Andersen et al, 2012;Windham et al, 1997). In the study by Andersen and colleagues, no increased risk was found after week 16, implying that the fetus is most vulnerable to alcohol exposure during early pregnancy (Nybo-Andersen et al, 2012).…”
Section: Effects Of Alcohol Consumption During Pregnancymentioning
confidence: 99%
“…The Nigerian Health Policy recognizes the need to reduce the current high infant mortality rates, but people's belief and behavioral practices have not been adequately integrated into the health intervention [23]. Other determinant factors reported globally include; maternal obesity [9,24,25], diabetes [19,26], hypertension [14,23,26], drinking of alcohol during pregnancy especially within the first trimester [27,28], tobacco smoking during pregnancy [20] especially among singleton births [29]. Others include: HIV infection exposure [30] especially in developing countries [21], rural residence as well as Psychosocial Stressors [22].…”
Section: Determinant Factors Of Infant Mortalitymentioning
confidence: 99%